Unilateral Pulmonary Agenesis about a Case Revealed by an Acute Respiratory Infection in a Young Infant - S. Aimée Kissou; Souleymane B. W. Adjaba; Jacqueline Tamini; Hélène Traore (Hindawi Limited, 2023)
Pulmonary agenesis is a rare congenital anomaly of unknown cause, consisting of a complete absence of the lung parenchyma, bronchi, and vascularization. It may or not be associated with other malformations. The authors report a case of right pulmonary agenesis diagnosed in a four-month-old infant who had no previous pathological history and was growing well. The circumstance of discovery was respiratory distress during an infectious episode. The diagnosis was suspected on a standard chest X-ray and confirmed on a chest CT scan. There are no other associated defects. The evolution was good after antibiotic therapy. While bilateral pulmonary agenesis is incompatible with life, the unilateral form may remain unrecognized until adulthood. The prognosis depends mainly on the importance of the associated malformations.